Climate change, culture, and economics anthropological investigations - Wood, Donald C. (Emerald, 2015)
It is becoming increasingly difficult to deny that human activity is a factor in global climate change. This special volume of REA facilitates readers to better understand the ways in which people around the world have adapted (or failed to adapt) culturally to changing economic conditions caused by climate change. It focuses on specific situations in particular locations, showcasing (and confirming) the strength and value of intensive ethnographic or archaeological A<U+0302>?investigation. The authors discuss: 1) How has climate change affected production, distribution, or consumption at the local level? 2) Are environmental conservation and economic development mutually exclusive? 3) What roles can public and private institutions play in successful adaptation? 4) What kinds of parallels can be drawn between current social situations and those in the past with regards to climate change?
Keywords: Climatic changes -- Research.; Climatic changes -- History.; elektronické knihy; electronic books